SISTEM TANGGAP DARURAT KEBAKARAN DI GEDUNG ADMINISTRASI PERUSAHAAN LISTRIK - Milla Rosa Mufida; Tri Martiana (The Indonesian Journal of Occupational Safety and Health, 2019)
Fire is an accident that can cause many losses. One of building safety requirements are application system of fire emergency response. The building contained a safety against fire hazard through the protection system of active and passive protection. This research aims to study fire emergency response system the administration building of PT PJB UP. PAITON in 2015. The variables are policy, procedures, organization, simulation training, communication and emergency response system for prevention and mitigation fires. The system of fire prevention and countermeasure are active and passive protection system. This was an observational study with cross-sectional design. This study was comparing the data observations and interviews with regulation Health Ministry of Indonesia 2010, international standard NFPA 10, 13, 14 and 72 and Kepmen PU No. 10/KPTS/2000. The result show that building have 4th floor and more than 200 employee, so need protection when there are fire building. Policy, procedure and organization unresolved by management industry. Simulation training has routine every 1 year. Communication of emergency response are good action. Active protection system are sufficient compliance with the standard. Passive protection system exist that do not meet the requirements. The results show that emergency response management system fire and fire prevention and countermeasure system still needs to be improved, especially in the management system. Keywords: administration building, electrical industry, fire emergency response system